2023
DOI: 10.3390/cancers15061818
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Promote Osteosarcoma Progression and Invasiveness via AKT/PI3K Signaling

Abstract: Background: Osteosarcoma (OS) mortality is attributed to lung metastases. Endothelial progenitor cells (EPCs) mediate the angiogenic switch in several cancers. The spatial proximity between EPCs and OS in the bone led to the hypothesis that EPCs-osteosarcoma interactions may possibly promote OS progression and aggressiveness. Methods: A PI3K inhibitor, Bevacizumab (an anti-VEGF-A antibody), and an anti-FGF2 antibody were added to the EPCs’ conditioned medium (EPC-CM), and their impacts on OS cell (U2-OS and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…AKT phosphorylates several substrates and downstream effectors, including mTOR, matrix metalloproteinase (MMP), cyclin-dependent kinases (CDKs), and VEGF, associated with tumor progression and metastasis [44,45]. The secretion of VEGF-A and FGF2 from OS cells promotes migration and invasion by activating the PI3K and AKT pathways, eventually leading to MMP9 overexpression [46]. Human epidermal growth factor receptor 4 (HER4), a member of the ERBB family, is upregulated in OS tumor tissue and cell lines, promoting OS progression by inactivating the PTEN-PI3K/AKT pathway [47].…”
Section: Pik3/akt/mtor Pathwaymentioning
confidence: 99%
“…AKT phosphorylates several substrates and downstream effectors, including mTOR, matrix metalloproteinase (MMP), cyclin-dependent kinases (CDKs), and VEGF, associated with tumor progression and metastasis [44,45]. The secretion of VEGF-A and FGF2 from OS cells promotes migration and invasion by activating the PI3K and AKT pathways, eventually leading to MMP9 overexpression [46]. Human epidermal growth factor receptor 4 (HER4), a member of the ERBB family, is upregulated in OS tumor tissue and cell lines, promoting OS progression by inactivating the PTEN-PI3K/AKT pathway [47].…”
Section: Pik3/akt/mtor Pathwaymentioning
confidence: 99%
“… 26 , 27 One such strategy is the use of circulating endothelial progenitor cells (EPCs), which can differentiate into mature endothelial cells and promote endothelial repair. 28 Studies have shown that the transplantation of EPCs can improve endothelial function and reduce neointimal hyperplasia in animal models of stent implantation. In summary, the adhesion, proliferation and migration, and cell death of endothelial cells are considered as the most important factors in the development of ISR.…”
Section: Introductionmentioning
confidence: 99%